Mathematical Model for Charter Flights Planning at Airports with High Air Traffic Volume - Graf, Vojtech; Teichmann, Dusan; Dorda, Michal (Communications - Scientific letters of the University of Zilina, 2016)
The article is devoted to a problem of flight timetable planning for charter airlines if air transport is operated at airports with high air traffic volume. It is typical for such airports that air transport is subject to time slots. That means aircraft can take-off or land only in given time intervals. A suitable tool for solving such type of the task is linear programming which has been successfully employed for planning in other transport systems. In the article a mathematical model which is able to plan a flight timetable for a given set of flights is presented.